DO ANIMOSITY, PRODUCT JUDGMENT, AND BOYCOTT PARTICIPATION INFLUENCE PURCHASE UNWILLINGNESS? - Fitri, Annisa; Listiana, Erna; Barkah, Barkah; Fitriana, Ana (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2024)
This study aims to examine the effect of animosity, product judgment, and boycott participation on purchase unwillingness of KFC products in Indonesia which is considered affiliated with Israel. The background of this study is the increasing consumer boycott movement in Indonesia due to the Israeli-Palestinian conflict. This study uses a survey method with a questionnaire distributed to 182 respondents selected through purposive sampling techniques. Data were analyzed using the Structural Equation Modeling (SEM) method. The results of the study indicate that animosity has a significant effect on product judgment, boycott participation, and purchase unwillingness. This study found that boycott participation was proven to be a significant mediator in the relationship between animosity and purchase unwillingness. However, product judgment can’t mediate the relationship between animosity and purchase unwillingness.